GAMBARAN KESIAPAN SISTEM SURVEILANS TUBERKULOSIS DALAM MENDUKUNG UPAYA PENGENDALIAN TUBERKULOSIS RESISTEN OBAT (TB-RO) DI KABUPATEN BANYUMAS - Sonia Dwi Astuti; Devi Octaviana; Siwi Pramatama Mars Wijayanti (Kesmas Indonesia, 2018)
Background: TB-RO is a tuberculosis disease which is resistant to the first-line drugs caused by unfinished treatment. One of the effort to control TB-RO is by increasing in finding and recording the case through TB surveillance activities. The surveillance results will be used to plan the controlling programs of TB-RO. Purpose: To describe the preparedness of TB surveillance system for supporting the control attempt of TB-RO in Banyumas. Methods: The method in this reasearch was a qualitative with content analysis approach. Subject of this research was collected by using purposive technique, amounted to 7 informants. The data was collected by in-depth interviews, observation and document study. Results: The preparedness of the TB surveillance in Banyumas is still poor in their input subsystem because of the double burden and the lack of training in TB officials. The preparedness of TB surveillance in their process and output subsystem is good enough and support the controlling attempt of TB-RO in Banyumas. The implementation of TB surveillance has obstacles such as unreadiness of human resources and tardiness in reporting from Puskesmas and Hospitals. Conclusion: TB Surveillance System has a good preparedness in supporting the control attempt of TB-RO in Banyumas although there are lackness in their TB surveillance input subsystem. Sugestion: Public Health Office of Banyumas was expected to conduct an inventory of human resources to resolve deficiencies in TB surveillance input subsystems.